(untitled) (Baghdad Science Journal, 2018)
The toxicological risks and lifetime cancer risks associated with exposure to disinfection by-products (DBPs) including Halloacetic acids (HAAs) and trihalomethanes (THMs) compounds by drinking water in several districts in Wassit Province were estimated. The seasonal variation of HAAs and THMs compounds in drinking water have indicated that the mean values for total HAAs (THAAs) and total THMs (TTHMs) ranged from 43.2 to 72.4 mg/l and from 40 to 115.5 mg/l, respectively. The World health organization index for additive toxicity approach was non-compliant with the WHO guideline value in summer and autumn seasons and this means that THMs concentration has adverse toxic health effects. The multi-pathway of lifetime human health risk of cancer credited to THMs and HAAs in drinking water via three exposure routes for THMs and only one exposure route for HAAs was evaluated and found to be 6.13×10-4 and 1.78×10-4 respectively and these values were higher than the US.EPA range of concern limit of 1×10-6. The risk ratio of THAAs to TTHMs was 3.44. Also, the highest cancer risk was recorded for BDCM followed by DBCM, CF, TCAA, DCAA, and BF.